Clinical and electrophysiological follow-up of modafinil treatment for multiple sclerosis patients with fatigue symptom - Akdoğan, Özlem; Haki, Cemile; Turan, Ömer Faruk; Taşkapılıoğlu, Özlem (The European Research Journal, 2020)
Objectives: In our study, we investigated the effects of modafinil therapy on clinical and neurophysiological tests of multiple sclerosis (MS) patients with fatigue. Methods: The study was performed on 18 MS patients (16 females, 2 males) at Uludağ University School of Medicine, Department of Neurology, who are followed up according to Mc Donald’s criteria, who had 36 points or above based on the fatigue assesment scala (FAS), whose Beck depression inventory points were 16 and below, whose thyroid, liver and renal functions were evaluated as normal, and who had no systemic disorder. All patients had neurological examination and their expanded disability status scale (EDSS), fatigue impact scala (FIS) and multiple sclerosis quality of life (MSQoL-54) were evaluated. Somatosensory evoked potential (SEP), visual evoked potential (VEP), brainstem auditory evoked potential (BAEP), visual event related evoked potential (visual P300) were performed in our neurophysiology laboratory. After that the patients were given modafinil 100 mgr 1×1 (morning) for 1 week, the following weeks 2×1 (morning and noon). At the end of the 6 weeks of therapy the patients were called to the neurology polyclinic, and their neurological examinations, EDSS, FIS, MSQoL-54, SEP, VEP, BAEP and visual P300 were repeated. Results: When the patients’ previous and subsequent FIS and MSQoL-54 total scores were compared, a significant statistical difference was found. When all 3 subgroups of FIS (consciousness, physical and social) were evaluated after the modafinil therapy, a significant statistical decrease in previous and successive scores were found. It is found out that modafinil therapy improves life quality which is evaluated due to MSQoL-54 (p < 0.05). A significant statistical relation between the number of MS disease attacks and the three subgroups of MFIS was not figured out (p > 0.05). There were no statistically significant relation between the FAS, EDSS and Beck depression inventory scores before the modafinil therapy had been applied (p > 0.05). There was a statistically correlation between Beck depression inventory score and FIS’s social subgroup (p = 0.017). When the patient’s SEP, VEP, BAEP, visual P300 average test values before and after the modafinil therapy were compared, a statistically significant difference was not observed. Conclusions: In our study, it is found that modafinil therapy, which is used against fatigue, one of the MS disase’s most common symptom, has a positive impact on MS life quality and patients’ clinical symptoms of fatigue, although it has no effect on patients’ evoked potential methods (BAEP, SEP, VEP, visual P300) performed in neurophysiology laboratory.